Stop living in this land : go to the everlasting world of happiness : live there forever - U, Myong; Maum Suryonhoe (Arlington, MA : Cham Books, 2012)
In his 10th book about Truth, author Woo Myung breaks down our long-standing preconceptions and explains how a life and world of Truth is within our reach by changing our minds. He explains that the world we dream of but have given up on can be attained when one changes his human mind to the mind of Truth - the mind of the Universe.
Translated from Korean by members of the Maum Meditation Translation Team.
Keywords: Self-actualization (Psychology); Truth; Peace; Happiness; Maum Suryonhoe